Pemikiran Politik Sunni Sebagai Alat Legitimasi Kekuasaan - Toguan Rambe; Seva Mayasari (Jurnal Penelitian Medan Agama, 2020)
Sunni political doctrine plays an important role in government, sunni doctrine which tends to be an instrument of legitimacy of power, has a great impact with the government in putting relations between the authorities (government) and the people by prioritizing social harmony, of course social and political stability will be well maintained. the majority of which are represented by, Ibn Abi Rabi ', Ibn Taimiyah and al Ghazali and al Mawardi. This thinking is based on the background and tendencies of these Sunni figures in the political problems of the state faced in their time. They base their political theory on reality and the existing socio-political situation.